Empobrecimento e podzolização de solos lateríticos da bacia do Rio Negro e gênese dos podzóis na alta Bacia da Amazônia - Bueno, Guilherme Taitson [UNESP] (2009)
Podzols present spectacular morphology, with sandy horizons over less permeable and organo-metallic compartments. They occupy important surfaces of the upper Amazon basin, under the influence of perched watertables and reducing/acidic environments. This work focuses on: (i) lateritic soils impoverishment before podzolisation; (ii) hydromorphic podzol development on the plateaux and their latter incision; and (iii) podzol dynamics in the Rio Negro catchment scale. It associates geochemical, petrographic and mineralogical approaches, with investigations of soil catena and landscapes units. The increasing chemical but also particulate erosion of lateritic soils from the edge to the podzolised plateaux centre affect, separately, soils and saprolites. Selective dissolution of iron oxydes (hematite, then goethite), and ultimately of kaolinite, are associated with soil yellowing and impoverishment. In the saprolites, the groundwater promotes the material bleaching, and lateral flows, close to podzols, its eluviation. Chemical and physical erosions generate sandy horizons explored by podzolisation. River incisions into podzols enhance organic matter mineralisation, iron oxidation and the sand transport to the rivers. The apparition of podzols may preceed the formation of modern Amazon River system (2,5 Ma BP). Ultimate incisions of podzols restrict their spatial expansion and fill with white sands the Rio Negro sediment traps